PENGARUH TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SIDOARJO PERIODE 2002-2011 - ANAS QOHARUDIN (Universitas Negeri Surabaya, 2014)
Economic growth in Sidoarjo is influenced by various factors . The primary objective of this study was to determine how the influence of education on economic growth in Sidoarjo period 2002-2011